There's something about Mary - Farrelly, Peter 1956-; Farrelly, Bobby 1958-; Diaz, Cameron 1972-; Dillon, Matt 1964- (20th Century Fox Home Entertainment, 1998)
Thirteen years after a humiliating high-school episode of prom dates interrupts, angst-driven Ted is still crazy in love with Mary. Hoping for a second chance at wooing the girl of his dreams he hires sleazy private dick Pat Healy to track her down. However, after taking one look at Mary, Healy decides he wants her for himself before long, Mary's suitors are engaged in a "hair-raising" battle for her affections, and soon, the fur really flies?right out the window.